Análise de resíduos de pesticidas em farinha de trigo integral usando método QuEChERS modificado e determinação por LC-MS/MS - Bordin, Aline Benedetti (My University, 2015)
Due to the frequent use of agrochemicals, it is important to control the same. Thereby, instrumental analytical methods, particularly liquid chromatography analyzes, are able to qualitatively and quantitatively evaluate mixtures of these substances. The objective of this study was to develop and validate a method of extraction for simultaneous determination of pesticide residues in whole wheat flour. The QuEChERS method was modified in the extraction stage using in place of magnesium sulfate, sodium sulfate in the first step also the modified method not performed the step of clean up. After the modified method was validated and the chromatographic conditions used. For the extraction was used acetonitrile with 1% acetic acid, sodium sulfate, sodium acetate and sodium citrate sesquihydrate. Was not carried out the clean up step. The method was validated by evaluating the following parameters: selectivity, linearity, limit of detection, limit of quantification, precision, accuracy and robustness. The linear range evaluated in this study was 1.0 to 200 mg L-1. Agrochemicals analyzed showed r² of at least 0.99 is considered acceptable by the rules of ANVISA. The quantification limit of the modified QuEChERS method showed equal and/or lower than the maximum residue limits established by Brazilian legislation (ANVISA) values. Of agrochemicals analyzed in whole wheat flour, 84% presented with percentage recovery between 70-120%, with repeatability and intermediate precision with RSD ≤ 20%. The 2,4-D agrochemicals, Cartap Hidrocloride, Cyproconazole, Ethyl Paraquat, Parathion-methyl and fenitrothion, were not quantified with safety in fortification levels evaluated presenting mean recovery values outside the reliable range for residue analysis. Evaluating the samples collected in Serra Gaucha region, all agrochemicals detected in wholewheat flour, were carbendazim, chlorpyrifos, Deltamitrina, Imidacloprid, Malathion, Pendimentalina, Pirimiphos-methyl, and Triamedifom Triadimenol, had values below the MRL established by ANVISA, Codex Alimentarius and the European Union. The developed and validated method was adequate and can therefore be applied in the determination of agrochemicals residues in whole wheat flour.
Devido ao uso frequente de agroquímicos, é importante o controle dos mesmos. Desta forma, métodos analíticos instrumentais, principalmente quando envolvem as análises por cromatografia líquida, são capazes de avaliar qualitativa e quantitativamente misturas destas substâncias. Assim, o objetivo deste trabalho foi desenvolver e validar um método de extração para determinação simultânea de resíduos de agroquímicos em farinha de trigo integral. O método QuEChERS foi modificado na etapa de extração, usando no lugar do sulfato de magnésio, o sulfato de sódio na primeira etapa, além disso o método modificado não realizou a etapa de clean up. Após foi validado o método modificado e as condições cromatográficas utilizadas. Para a extração foi usado acetonitrila contento 1% de ácido acético, sulfato de sódio, acetato de sódio e citrato de sódio sesquihidratado. Na etapa de validação foi seguido os seguintes parâmetros: seletividade, linearidade, limite de detecção, limite de quantificação, precisão, exatidão e robustez. A faixa linear avaliada neste trabalho foi de 1,0 a 200 μg L-1. Os agroquímicos analisados apresentaram r² de no mínimo 0,99, foi considerado aceitável pelas normas da ANVISA. O limite de quantificação do método apresentou valores iguais e/ou menores que os limites máximos de resíduos estabelecidos pela legislação brasileira (ANVISA). Dos agroquímicos analisados na farinha de trigo integral, 84% destes apresentaram percentuais de recuperação entre 70-120%, com repetibilidade e precisão intermediária com RSD ≤ 20%. Os agroquímicos 2,4-D, Cartap Hidrocloride, Ciproconazol, Etil Paraquat, Fenitrotiona e Parationa-metílica, não foram quantificados com segurança nos níveis de fortificação avaliados apresentando valores médios de recuperação, fora da faixa confiável para análise de resíduos. Avaliando as amostras coletadas na região da Serra Gaúcha, todos os agroquímicos detectados nas farinhas de trigo integrais, foram Carbendazim, Clorpirifos, Deltamitrina, Imidacloprido, Malationa, Pendimentalina, Pirimifos-metil, Triamedifom e Triadimenol, apresentaram valores abaixo do LMR estabelecido pela ANVISA, Codex Alimentarius e União Européia. O método desenvolvido e validado mostrouse adequado podendo assim ser aplicado na determinação de resíduos de agroquímicos em de farinha de trigo integral.
Keywords: Produtos químicos agrícolas; Produtos químicos; Trigo; Pesticidas; Agricultural chemicals; Chemicals; Wheat; Pesticides